Expression of the Circadian Clock Gene BMAL1 Positively Correlates With Antitumor Immunity and Patient Survival in Metastatic Melanoma - de Assis, Leonardo Vinícius Monteiro; Kinker, Gabriela Sarti; Moraes, Maria Nathália; Markus, Regina P.; Fernandes, Pedro Augusto; Castrucci, Ana Maria de Lauro (Frontiers in Oncology, 2018)
Melanoma is the most lethal type of skin cancer, with increasing incidence and mortality rates worldwide. Multiple studies have demonstrated a link between cancer development/progression and circadian disruption; however, the complex role of tumor-autonomous molecular clocks remains poorly understood. With that in mind, we investigated the pathophysiological relevance of clock gene expression in metastatic melanoma. Methods: We analyzed gene expression, somatic mutation, and clinical data from 340 metastatic melanomas from The Cancer Genome Atlas, as well as gene expression data from 234 normal skin samples from Genotype-Tissue Expression. Findings were confirmed in two independent datasets. Results: In melanomas, the expression of most clock genes was remarkably reduced and displayed a disrupted pattern of co-expression compared to the normal skins, indicating a dysfunctional circadian clock. Importantly, we demonstrate that the expression of the clock gene BMAL1 positively correlates with patient overall survival and with the expression of T-cell activity and exhaustion markers in the tumor bulk. Accordingly, high BMAL1 expression in pre-treatment samples was significantly associated with clinical benefit from immune checkpoint inhibitors. The robust intratumoral T-cell infiltration/activation observed in patients with high BMAL1 expression was associated with a decreased expression of key DNA repair enzymes, and with an increased mutational/neoantigen load. Conclusions: Overall, our data corroborate previous reports regarding the impact of BMAL1 expression on the cellular DNA repair capacity and indicate that alterations in the tumor-autonomous molecular clock could influence the cellular composition of the surrounding microenvironment. Moreover, we revealed the potential of BMAL1 as a clinically relevant prognostic factor and biomarker for T-cell-based immunotherapies.